KENDALI BERBASIS WEB PADA ANOMALI NEUTRAL GROUND RESISTOR (NGR) - Kiswantono, Agus (Universitas Lampung, 2024)
A real-time monitoring and control system for Neutral Grounding Resistor (NGR) has been developed utilizing Internet of Things (IoT) technology. The system employs the PZEM-004T sensor for measuring current and voltage, and the NodeMCU ESP8266 for data processing and communication. Measurement data is displayed in real-time on an LCD screen and a website, with early warning alerts provided through a buzzer/alarm if abnormal conditions are detected. This system addresses the limitations of traditional monitoring methods, which are typically visual and periodic, by enabling continuous monitoring. Integration with a circuit breaker adds an additional layer of protection by disconnecting the power supply when necessary. Testing results demonstrate the effectiveness of the device in measuring voltages ranging from 5V to 220V and current, with a reliance on internet connectivity to ensure measurement accuracy. This system offers an efficient and proactive solution for maintaining the safety and reliability of electrical equipment at substations